California schemin' - Keene, Carolyn (Keene, Carolyn. Nancy Drew, girl detective, 2011)
When Nancy and her friends vacation in a California beach house, they discover someone is dumping trash on the beach, and Nancy suspects both reality show sisters the Casabians and a suspicious owner of a spa.